“Evaluación al cumplimiento tributario a la empresa inginost cía. ltda. de la ciudad de Riobamba para determinar la veracidad del pago del impuesto a la renta en el año 2014” - Zamora Berrones, Verónica Elizabeth (2017)
The was developed to identify the level of compliance with the Tax Administration with respect to the obligations indicated in the single register of taxpayers of the company. In this goal we began with the identification of its problem that served to define the objectives of study. It took general information of the company to know the context of its activity and basic internal aspects. In relation with the research variables, the information contained in Laws, Regulations and Instruction was used to regulate the obligations of legal persons according to their activity. The research used the inductive method, non-experimental design, document type, field and an exploratory level; information required for the study was obtained through the observation of accounting, financial and tax information, interviews applied to the study population. The results were analyzed, discussed and were the basis for the elaboration of conclusions and recommendations.